2016
DOI: 10.1002/mnfr.201500766
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from cancer prevention studies with nutrients and non‐nutritive dietary constituents

Abstract: Epidemiological studies have observed the association between dietary patterns and the risk of certain types of cancer. Extensive studies have been conducted on the cancer preventive activities of constituents from food and beverages. While laboratory research has shown impressive and promising results, such promising cancer preventive activities have not been demonstrated in many human intervention trials. This article analyzes the major differences between these different types of studies and the limitations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 98 publications
1
31
0
Order By: Relevance
“…Published reviews detail the many rodent studies documenting the ability of GT extract or GT polyphenol consumption to prevent digestive tract tumors [ 6 , 7 ]. Studies of the oral cavity and the esophagus include usage of hamster, rat, and mouse models to show that GT extract or purified polyphenols in drinking water can inhibit the induction of tumors by various carcinogens at both sites [ 8 , 9 , 10 , 11 , 12 , 13 ]. Additional studies show efficacy of GT in preventing cancer of the colon and liver, and non-digestive tract sites such as prostate and lung, and that this inhibition can occur whether the GT or GT polyphenols are present during or after carcinogen exposure [ 2 , 14 , 15 ].…”
Section: Gt Inhibition Of Rodent Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Published reviews detail the many rodent studies documenting the ability of GT extract or GT polyphenol consumption to prevent digestive tract tumors [ 6 , 7 ]. Studies of the oral cavity and the esophagus include usage of hamster, rat, and mouse models to show that GT extract or purified polyphenols in drinking water can inhibit the induction of tumors by various carcinogens at both sites [ 8 , 9 , 10 , 11 , 12 , 13 ]. Additional studies show efficacy of GT in preventing cancer of the colon and liver, and non-digestive tract sites such as prostate and lung, and that this inhibition can occur whether the GT or GT polyphenols are present during or after carcinogen exposure [ 2 , 14 , 15 ].…”
Section: Gt Inhibition Of Rodent Cancermentioning
confidence: 99%
“…Plasma and cellular levels of intact catechins are often quite low due to poor uptake by gut epithelium, compared to concentrations used in in vitro studies, as commented on by Yang and Wang [ 4 ]. The major tea catechins including EGCG, as predicted by Lipinski’s rule of five, due to large size, presence of hydrated shells, and their polarity, are poorly absorbed by cells [ 4 , 13 , 35 , 36 , 37 ]. In the case of oral epithelium, which is exposed to undiluted GT in tea drinkers, concentrations of catechins are high, hundreds of micrograms per mL, but exposure is transient, so absorption of the unaltered molecules into cells is suboptimal.…”
Section: Significance Of Studying Gt Effects In Vivomentioning
confidence: 99%
“…For all of the above groups, examples are known for both carcinogenic and preventive effects, like carcinogenic (e.g., red meat, [29]) or anticarcinogenic food (tea extracts, [30]); carcinogenic (e.g., vitamin A and ß carotene, [31]) or preventive food supplements (e.g., herbal preparations, [32]), or chemopreventive chemicals (e.g., NSAIDS and colon cancer, [33]); the number of proven or putative carcinogens among chemicals is very high.…”
Section: Current Concepts Of Chemopreventionmentioning
confidence: 99%
“…Furthermore, some recent studies suggested that vitamin E and analog promoted lung cancer progression [ 14 ] and melanoma metastasis in mice [ 15 ]. The interpretation of these results may vary and the cancer preventive activities of tocopherols are still unclear [ 5 , 16 ].…”
Section: Introductionmentioning
confidence: 99%